2006
DOI: 10.1111/j.1574-6941.2006.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of n-hexadecane in soil by thermophilic geobacilli

Abstract: Soil microcosms have been used to demonstrate the ability of indigenous soil thermophiles to degrade effectively a representative alkane (n-hexadecane). A fragment of the alkane mono-oxygenase gene (alkB) was amplified from thermophilic Geobacillus thermoleovorans strain T70 by PCR using degenerate primers. The amplicon demonstrated 96% sequence similarity with the alkB gene from Rhodococcus erythropolis. Critical controls ensured that the positive PCR signal detected was not a result of mesophilic soil organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 27 publications
1
41
0
5
Order By: Relevance
“…More recently, Bacillus, Geobacillus (phylum Firmicutes) and Thermus (phylum Deinococcus-Thermus) isolates were found to degrade alkanes (Marchant et al, 2006;Meintanis et al, 2006). The best diesel degrading Gram-positive microorganisms (D2, D9, D10) isolated in this study were identified as Paenibacillus sp.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…More recently, Bacillus, Geobacillus (phylum Firmicutes) and Thermus (phylum Deinococcus-Thermus) isolates were found to degrade alkanes (Marchant et al, 2006;Meintanis et al, 2006). The best diesel degrading Gram-positive microorganisms (D2, D9, D10) isolated in this study were identified as Paenibacillus sp.…”
Section: Discussionmentioning
confidence: 90%
“…Microorganisms capable of surviving on these highly reduced organic compounds have been identified (Marchant et al, 2006). More recently, Bacillus, Geobacillus (phylum Firmicutes) and Thermus (phylum Deinococcus-Thermus) isolates were found to degrade alkanes (Marchant et al, 2006;Meintanis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…pGAM47-bgaB pUC19 derivative; pUC replicon, oriT, bla, pyrF, P sigA -bgaB lanked by gk0707 upstream and downstream regions [19] pGAM48-bgaB pUC19 derivative; pUC replicon, oriT, bla, pyrF, P gk704 -bgaB lanked by gk0707 upstream and downstream regions [21] pGKE25 pUC19 derivative; pUC replicon, oriT, bla, pyrF [20] pGKE25-bgaB pGKE25 derivative; pUC replicon, oriT, bla, pyrF, P sigA -bgaB lanked by gkp09 upstream and downstream regions This study pUCG18T pUC18 derivative; pUC and pBST1 replicons, oriT, bla, TK101…”
Section: Relevant Description Referencementioning
confidence: 99%
“…The whole genome sequence has been determined [17], showing that G. kaustophilus HTA426 harbors the circular plasmid pHTA426 (Figure 1). Because the members of the genus Geobacillus include strains that are useful for high-temperature processes, as demonstrated by strains that are capable of degrading hydrocarbons [18], long-chain alkanes [19][20][21], biphenyls [22], parain-wax [23], or nylons [24], we have studied biotechnological applications of the genus using G. kaustophilus HTA426 as a model and pilot strain.…”
Section: Archaea -New Biocatalysts Novel Pharmaceuticals and Variousmentioning
confidence: 99%
“…We will also investigate the aspect of production of biosurfactants as an additional property of some thermophilic degrader microorganisms for further enhancing hydrocarbon removal. Some of these aspects have been introduced in recent publications [17][18][19]26]. …”
Section: Introductionmentioning
confidence: 99%